2021
DOI: 10.1161/jaha.120.020364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart Rate Variabilities on Outcome After Acute Intracerebral Hemorrhage: A Post Hoc Analysis of ATACH‐2

Abstract: Background To explore how the clinical impact of heart rate (HR) and heart rate variabilities (HRV) during the initial 24 hours after acute intracerebral hemorrhage (ICH) contribute to worse clinical outcomes. Methods and Results In the ATACH‐2 (Antihypertensive Treatment in Intracerebral Hemorrhage 2) trial, the HR was recorded for every 15 minutes from baseline to 1 hour and hourly during the initial 24 hours post‐randomization. We calculated the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Numerous studies have found that heart rate was associated with the prognosis of many diseases, including coronary heart disease, myocardial infarction, heart failure, acute ischemic stroke, acute hemorrhagic stroke, and so on ( 7 , 9 , 11 , 13 , 27 30 ). In addition, heart rate variability is associated with the incidence and duration of poststroke depression ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have found that heart rate was associated with the prognosis of many diseases, including coronary heart disease, myocardial infarction, heart failure, acute ischemic stroke, acute hemorrhagic stroke, and so on ( 7 , 9 , 11 , 13 , 27 30 ). In addition, heart rate variability is associated with the incidence and duration of poststroke depression ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A fast heart rate may also indicate sympathetic nerve overactivity, which has been related to inflammatory processes and higher blood pressure at night, both of which are well-known indicators of stroke mortality ( 35 37 ). Previous studies on the relationship between heart rate variability and stroke outcomes have also found that patients with low heart rate variability have a worse prognosis, while low heart rate variability indicates high sympathetic nervous system activity ( 8 , 10 , 11 ). In addition to the increased sympathetic nervous system tone in the acute phase of stroke, Lee et al found a stronger association between mean heart rate and mortality in the late acute stage ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Japanese researchers contributed to the ATACH-2 trial not only by patient recruitment but also by subanalyses using the ATACH-2 dataset. The themes of the subanalyses included sex differences [ 29 ], regional differences (Asia versus non-Asia) [ 30 ], late neurological deterioration [ 31 ], kidney function [ 32 ], heart rate [ 33 ], and the impacts of achieved SBP levels on clinical outcomes [ 34 ].…”
Section: Moving On To the Atach-2 Trialmentioning
confidence: 99%